Psychometric properties of Persian version of Cognitive Behavioural Avoidance Scale: results from student, general population and clinical samples in Iran. Issue 6 (6th November 2020) - Moloodi, Reza; Dobson, Keith; Fata, Ladan; Pourshahbaz, Abbas; Mohammadkhani, Parvaneh; Mootabi, Fereshteh; Kami, Maryam; Ziai, Kaveh; Ghaderi, Ata
Abstract: Background: There is no published evidence about the psychometric properties of the Cognitive Behavioral Avoidance Scale (CBAS) in Eastern cultures. Aims: The current research evaluated the psychometric properties of a Persian version of the CBAS. Method: The research consisted of two studies. In Study 1, a university student sample ( n = 702) completed the CBAS, the Beck Depression Inventory-II, the Thought Control Questionnaire and the Anxious Thoughts Inventory. In Study 2, a general population sample ( n = 384) and a clinical sample ( n = 152) completed the CBAS, the Young Compensation Inventory and the Depression, Anxiety, Stress Scale-21. Results: Exploratory factor analysis of the data from Study 1 suggested a four-factor solution for CBAS. The CBAS had acceptable internal consistency and test–re-test reliability, and showed significant correlations with depression symptoms and anxious thoughts. Confirmatory factor analysis of the data from Study 2 indicated good fit between the four-factor model and data. The CBAS had a significant relationship with depression, anxiety and stress symptoms, but no associations with schema compensatory behaviour strategy. Finally, the CBAS and its subscales successfully distinguished a clinical sample from a general population sample. Conclusions: The findings provide preliminary evidence for reliability and validity of the CBAS among Iranian student, general population and clinical samples.